Design of heat exhanger network using pinch method - Wan Mansor, Wan Nurdiyana (2006)
Chemical or oil refineiy processes utilize huge amounts o f energy in their routine operations. Therefore, it is vital for such industries to find ways o f maximizing the use of energy and make the system more efficient through reduction in energy, water and raw material consumption. Waste energy can be transferred to another process and that will increase the profitability of the industries. When the use of a heat exchanger network (HEN) is considered for these tasks, the framework developed in this study can be implemented to make a cost-benefit analysis. This thesis represents a framework for generating the H E N over a specified range of variations in the f l ow rates and temperature o f the streams. So that the heat exchanger area, number o f heat exchange units and load on the heat exchangers can be estimated. The proposed method to analyze and design the H E N is called pinch method, which is one o f the most practical tools and used to improve the efficiency o f energy usage, fuel and water consumption in industrial processes. This method investigates the energy flows within a process and identifies the most economical ways of maximizing heat recovery. This method consists o f five major steps to follow, which will finally lead to H E N design. The steps are: (1) choose a minimum temperature approach temperature (DTmin), (2) construct a temperature interval diagram, (3) construct a cascade diagram and determine the minimum utility requirements and the pinch temperature, (4) calculate the minimum number o f heat exchangers above and below the pinch and (5) construct the heat exchanger network. The emphasis of this work has been on the designing of the H E N . However, to demonstrate the practical implications of pinch analysis, D T m i n and the heat exchanger costs, it is necessary to estimate the heat transfer area o f the H E N , which will help in arriving at the total cost including capital and running costs o f the designed H E N . The effect o f changing the D T m i n gave a good indication on the overall costs.